Long Term Effectiveness of Photodynamic Therapy for CIN Treatment - Natalia Mayumi Inada; Hilde Harb Buzzá; Marieli Fernanda Martins Leite; Cristina Kurachi; Jose Roberto Trujillo; Cynthia Aparecida de Castro; Fernanda Mansano Carbinatto; Welington Lombardi; Vanderlei Salvador Bagnato (MDPI AG, 2019)
(1) Background: Cervical cancer is the third most commonly diagnosed cancer and the fourth leading cause of cancer death in women worldwide. The highest incidence rates are in Africa, followed by South-Central Asia and South America. According to the Brazilian National Institute of Cancer (INCA), 16,370 new cases of cervical cancer were estimated for each year of the biennium of 2018−2019. About 90% of cervical cancers originate from the malignant progression of cervical intraepithelial neoplasia (CIN) which is classified based on cytohistological characteristics (low- and high-grade lesions). The present study reports the long-term effectiveness of topical photodynamic therapy (PDT) for CIN grades 1 and 2/3 with up to two years of follow up. (2) Methods: A total of 56 patients with CIN 1, ten with CIN 2, and 14 patients for the placebo group were enrolled in this study. (3) Results: 75% (n = 42) of CIN 1 patients presented a complete response to PDT and only 23.2% (n = 13) of recurrence, progression, and/or lesions remaining two years after PDT. For CIN 2/3 patients, 90% were observed to be cured after one and two years of follow up. (4) Conclusions: PDT presented best results two years after a non-invasive, fast, and low-cost procedure and in comparison with the placebo group, preventing the progression of cervical intraepithelial neoplasia and preserving the cervix.